The patient and the relation between power-knowledge and care by nursing professionals - Marina Kelly Santos Baptista; Regina Maria dos Santos; Sebastião Junior Henrique Duarte; Isabel Comassetto; Maria Cristina Soares Figueiredo Trezza (Universidade Federal do Rio de Janeiro, 2017)
Abstract This is a study whose objective was to analyze, in the discourse of hospitalized patients, how the power of knowledge is revealed in Nursing care relations. It was developed in the qualitative perspective, having as theoretical reference the concept of power issued by Michel Foucault. The data were collected between August and December 2015 and the participants were 16 patients hospitalized in the medical and surgical clinics of a university hospital, who had the speech recorded through a semi-structured interview, after approval of the ethics committee under Opinion No. 1189934. In order to analyze the data we used the system of differentiations developed by Foucault. The results showed that the professionals exert power by the highly specialized professional knowledge and that they know what they do, so they send and control the accomplishment of the care, leading the patient to submission. It concludes that the exercise of the power to care must be based on the observance of ethical and bioethical principles.